The Buddha's single intention Drigung Kyobpa Jikten Sumgön's Vajra statements of the early Kagyü tradition - Sobisch, Jan-Ulrich 1962-; Chökyi Drakpa Rikzin 1595-1659; Vjig-rten-mgon-po 1143-1217 (Studies in Indian and Tibetan Buddhism, 2020)
Cover Page -- Title Page -- Contents -- Foreword -- Preface -- Introduction -- Light of the Sun by Rikzin Chökyi Drakpa -- Preliminaries -- 1. The Vital Points of the Dharma Wheel -- 2. The Vital Points of Dependent Origination -- 3. The Vinaya-Prātimokṣa -- 4. The Training of the Bodhisattvas -- 5. The Observance of Mantra Awareness Holders -- 6. View, Practice, and Conduct -- 7. The Resultant State of Buddhahood -- 8. Supplements -- Appendix: Commentaries of the Single Intention -- Table of Tibetan Transliteration -- Bibliography -- Index -- About the Author -- Copyright